Environmental Tax Reforms in Switzerland: A Computable General Equilibrium Impact Analysis - Christoph Böhringer; André Müller (Swiss Journal of Economics and Statistics, 2014)
The Swiss energy strategy until 2050 envisages ambitious CO2 emission reduction targets along with substantial cutbacks in electricity consumption to establish a low-carbon economy without nuclear energy. Our computable general equilibrium analysis finds that compliance with stringent CO2 constraints requires high CO2 taxes on economic activities which are not eligible for international emissions trading; likewise, electricity consumers are burdened with substantial electricity taxes. Environmental tax reforms are not likely to generate welfare gains without accounting for the benefits of improved environmental quality. However, economic adjustment costs to a low carbon economy without nuclear energy remain modest and can be markedly reduced through revenue-neutral cuts of initial distortionary taxes. On the other hand, alternative recycling strategies pose a trade-off between efficiency and distributional justice which has to be resolved on normative grounds.
Keywords: H21; D58; Q48; 330; environmental tax reforms; computable general equilibrium